Semiotic Analysis of Charless Sanders Pierce Construction of Mental Meaning Breakdown: Analisis Semiotika Charless Sanders Pierce Konstruksi Makna Mental Breakdown - Nursadapu, Dhea Novita; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to describe what the meaning of what is stored in the Youtube channel by reviewing about mental break down, which is often also considered negative by most people, especially in Indonesia itself. One episode on the YouTube channel